2008
DOI: 10.3201/eid1409.071576
|View full text |Cite
|
Sign up to set email alerts
|

Pigs as Source of Methicillin-ResistantStaphylococcus aureusCC398 Infections in Humans, Denmark

Abstract: An emerging subtype of methicillin-resistant Staphylococcus aureus (MRSA), clonal complex (CC) 398, is associated with animals, particularly pigs. We conducted a matched case-control and a case-case study comparing 21 CC398 case-patients with 2 controls randomly selected from the Danish Civil Registry and 2 case-patients infected with MRSA other than CC398. On farms of case-patients, animals were examined for MRSA. Thirteen case-patients reported pig exposure. Living or working on farms with animals was an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
189
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(209 citation statements)
references
References 33 publications
(45 reference statements)
8
189
2
5
Order By: Relevance
“…For livestock CC398 (sequenced by Schijffelen et al, 2010, andUhlemann et al, 2012), our study demonstrated that this clade has undergone a host transition from originally humans to animals, mainly pigs and calves (van Loo et al, 2007;Lewis et al, 2008). However, as the present study demonstrates, CC398 is also a pathogen of bovine IMI.…”
Section: Clonality Of Bovine Strains and Phylogeneticscontrasting
confidence: 41%
“…For livestock CC398 (sequenced by Schijffelen et al, 2010, andUhlemann et al, 2012), our study demonstrated that this clade has undergone a host transition from originally humans to animals, mainly pigs and calves (van Loo et al, 2007;Lewis et al, 2008). However, as the present study demonstrates, CC398 is also a pathogen of bovine IMI.…”
Section: Clonality Of Bovine Strains and Phylogeneticscontrasting
confidence: 41%
“…2,8,19,24,36,38,42,43 Of note, the BORSA and MRSA strains of our study did not appear to be particularly more virulent than other S. aureus in horses. Infected equine patients did not suffer from increased frequency or severity of complications in wound healing, nor did colonized humans develop clinical signs.…”
Section: Discussionmentioning
confidence: 88%
“…Antimicrobial-resistant bacteria may also transfer from animals to humans though direct contact. This is, for example, the case for MRSA CC398 where transmission frequently occurs from the animals to the farmers or other people in contact with the animals [37].…”
Section: (Iv) Macrotransmission Of Resistancementioning
confidence: 99%